Third Five-Year Plan Progress Report for the Period Ending September 1963 Bihar - Planning Commission (Planning Commission, 1963)
Statement Showing Progress Of Plan Expenditure Under The Major Heaps Of Development For The Quarter Ending 30Th September 1963. Statement Showing Progress Of Plan Expenditure For The Quarter Ending 30Th September 1963. Statement Showing Progress Of Plan Expenditure For The Quarter Ending 30Th September 1963—Contd Statement Showing Progress Of Plan Expenditure For The Quarter Ending 30Th September 1963-Contd
Printed by the Superintendent Secretariat Press Bihar Patna 1965.